The Role of Colistin in the Era of New β-Lactam/β-Lactamase Inhibitor Combinations - Abdullah Tarık Aslan; Murat Akova (MDPI AG, 2022)
With the current crisis related to the emergence of carbapenem-resistant Gram-negative bacteria (CR-GNB), classical treatment approaches with so-called "old-fashion antibiotics" are generally unsatisfactory. Newly approved β-lactam/β-lactamase inhibitors (BLBLIs) should be considered as the first-line treatment options for carbapenem-resistant Enterobacterales (CRE) and carbapenem-resistant Pseudomonas aeruginosa (CRPA) infections. However, colistin can be prescribed for uncomplicated lower urinary tract infections caused by CR-GNB by relying on its pharmacokinetic and pharmacodynamic properties. Similarly, colistin can still be regarded as an alternative therapy for infections caused by carbapenem-resistant Acinetobacter baumannii (CRAB) until new and effective agents are approved. Using colistin in combination regimens (i.e., including at least two in vitro active agents) can be considered in CRAB infections, and CRE infections with high risk of mortality. In conclusion, new BLBLIs have largely replaced colistin for the treatment of CR-GNB infections. Nevertheless, colistin may be needed for the treatment of CRAB infections and in the setting where the new BLBLIs are currently unavailable. In addition, with the advent of rapid diagnostic methods and novel antimicrobials, the application of personalized medicine has gained significant importance in the treatment of CRE infections.